Surgical treatment of postoperative intractable bile leakage after liver tumor surgery in children - Han, Jianyu; Qin, Hong; Yang, Wei; Cheng, Haiyan; Chang, Xiaofeng; Zhu, Zhiyun; Feng, Jun; Yang, Shen; Chen, Yajun; Wang, Huanmin (Frontiers in Pediatrics, 2023)
Aim: To summarize systematically our six-year experience in the surgical treatment of postoperative bile leakage after liver tumor surgery in children, and explore its reoperation approach and treatment effect. Methods: The clinical data of 6 patients with postoperative bile leakage cured by surgery from January 2016 to January 2022 were reviewed retrospectively. Results: Among the six pediatric patients with postoperative bile leakage cured by surgery, four were male (67%) and two were female (33%). All patients underwent complex segmentectomy. The median time to bile leakage was 14 days (range, 10 to 32), and the daily drainage volume was stable from 170 ml to 530 ml per day. After conservative treatment failed, four patients received biliary-enteric anastomosis (patients 1, 3, 4, and 6), and two patients received bilio-cholecyst anastomosis (patients 2 and 5). All six patients were successfully treated with reoperation, and five patients were alive and without recurrence, while one patient was lost to follow-up due to abandoned treatment. Conclusion: Our study suggests that surgery is a reliable and effective treatment for postoperative intractable bile leakage in children undergoing complex segmentectomy. Bilioenteric anastomosis is the most common technique for bile leakage, and bilio-cholecyst anastomosis is a feasible and effective surgical approach. These findings have important implications for the management of postoperative complications in pediatric patients undergoing complex segmentectomy.